“Parque do cocó”: diretrizes para a proteção de relevante área verde no município de Fortaleza/CE - Azevedo, Ruy Emmanuel Silva de (2014)
The Cocó river and its surroundings have a singular peculiarity, because they meet an area of great ecological relevance stuck in a fairly densely populated urban area. This work was motivated by the fact that the area known as "Park of Cocó" not having adequate environmental management, since the State Park protected area was not created. There is only one polygon extracted from state decrees (n. 20.259/1989, 21.312/1991 and 22.587/1993), whose purpose was to declare certain areas as social interest so that after expropriated, were intended to create the park. Such decrees are not legally created the PA, since its purpose was only effecting the expropriation. Over the years the state expropriation decrees expired, foreclosures were not realized and protected area was not legally created. Meanwhile, there was a significant change in the urban context of the city of Fortaleza, and changes in the relevant legislation, which entails a necessary revision of the polygon that would be the " Park of Cocó". In this scenario, the study proposes criteria and requirements to be observed in the creation of a new category of protected area. Furthermore, the dissertation, based on environmental characterization and legal institutions incidents in the area (urban zoning, permanent preservation areas and marine land), proposes guidelines for the guidance of the boundary of a polygon that is technically feasible for the type of conservation unit applicable to the study area. The survey was conducted through literature review and documentary, interpretation and manipulation of cartographic vector files and field surveys. After analyzing the data, the paper proposes that the "basic area" of the future UC is defined based on the existence of the following legal institutions: areas of permanent preservation, marine lands areas and the most restrictive urban standards (ZPA 1 and ZRA) of the PDP-FOR/2009. The paper suggests that state of Ceará or the county of Fortaleza can create a legally adequate conservation unit and technically feasible through actions divided into five stages, which can be performed in sequence or in parallel. STAGE 0 corresponds to the preparatory phase, with review of cartographic vector files, lifting occupations and creating a type of compatible conservation unit. STAGE 1 would be the creation phase of UC with its "basic area" and should be expropriated the properties at ZPA 1 or ZRA that are not occupied or are occupied by public facilities (roads, squares and so on). STAGES 2 and 3 would be extensions of "basic research", by including areas that may give rise to relocation of people and the removal of occupations. When the properties are in marine lands, the Union may make use of free assignment of use for the creator entity of the UC (state of Ceará or the county of Fortaleza). And in STAGE 4 should integrate the management of protected areas in mosaic, covering the newly created UC and existing in its surroundings.